2021
DOI: 10.1002/14651858.cd013207.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care tests detecting HIV nucleic acids for diagnosis of HIV-1 or HIV-2 infection in infants and children aged 18 months or less

Abstract: Background The standard method of diagnosing HIV in infants and children less than 18 months is with a nucleic acid amplification test reverse transcriptase polymerase chain reaction test (NAT RT‐PCR) detecting viral ribonucleic acid (RNA). Laboratory testing using the RT‐PCR platform for HIV infection is limited by poor access, logistical support, and delays in relaying test results and initiating therapy in low‐resource settings. The use of rapid diagnostic tests at or near the point‐of‐care (PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Among infants with HIV diagnosed at birth who were initiated on ART, retention in care was high, comparable to retention in care for other children living with HIV, and higher than retention in care of infants identified as having HIV at birth using conventional testing. 3,15,19,20,24 In a 2022 randomized control trial comparing POC and central lab-based EID among HEI in Zambia, though not at birth, POC testing reduced delays in diagnosis and ART initiation, but both groups experienced high levels of care interruptions, virologic failures, and mortality at 12 months. 25 Recent model-based cost-effectiveness studies show investing in POC technology will be more cost-efficient for EID efforts than scaling up preexisting laboratory-based testing methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among infants with HIV diagnosed at birth who were initiated on ART, retention in care was high, comparable to retention in care for other children living with HIV, and higher than retention in care of infants identified as having HIV at birth using conventional testing. 3,15,19,20,24 In a 2022 randomized control trial comparing POC and central lab-based EID among HEI in Zambia, though not at birth, POC testing reduced delays in diagnosis and ART initiation, but both groups experienced high levels of care interruptions, virologic failures, and mortality at 12 months. 25 Recent model-based cost-effectiveness studies show investing in POC technology will be more cost-efficient for EID efforts than scaling up preexisting laboratory-based testing methods.…”
Section: Discussionmentioning
confidence: 99%
“…2 Infants who test positive for HIV often face delays in antiretroviral therapy (ART) initiation because of long turnaround times (TAT) for test results and loss-to-follow-up before results are returned. [3][4][5] Infants living with HIV who are untreated have a high risk for mortality, up to 10% at 2 months and 30%-40% between 3 and 4 months of age. 6,7 Early infant diagnosis (EID) of HIV and timely initiation of ART can significantly reduce mortality, limit the establishment of viral reservoirs, reduce HIV disease progression, and improve neurodevelopmental outcomes.…”
mentioning
confidence: 99%
“…Nucleic acid-based tests (NATs) are also used in HIV testing to detect HIV-1 and HIV-2 infections. These tests utilize DNA polymerase chain reaction (PCR) tests to detect integrated viral DNA and RNA reverse transcription PCR (RT-PCR) to detect viral RNA [ 17 ]. These tests allow for the more rapid diagnosis of HIV as they target the actual viral code as opposed to the ELISA discussed above, which relies on antibody production.…”
Section: Reviewmentioning
confidence: 99%
“…At present, there is no effective drug to cure AIDS. Therefore, the prevention of HIV infection, especially the high‐risk groups of HIV infection, is an important measure to control the AIDS epidemic 5 . WHO guidelines strongly recommend oral PrEP containing TDF as part of a combined HIV prophylaxis approach for people at high risk of HIV infection 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prevention of HIV infection, especially the high-risk groups of HIV infection, is an important measure to control the AIDS epidemic. 5 WHO guidelines strongly recommend oral PrEP containing TDF as part of a combined HIV prophylaxis approach for people at high risk of HIV infection. 6 Several randomized trials have shown that PrEP with daily oral TDF and emtricitabine (FTC) shows high efficacy among men who have sex with men and trans women, 7 heterosexual men and women, 8 and intravenous drug users.…”
Section: Introductionmentioning
confidence: 99%